Unconventional Oil Prospects and Challenges in the Covid-19 Era - Eveloy, Valerie; Elsheikh, Hassan (Frontiers in Energy Research, 2022)
Fossil fuels will continue to play an important role for the forthcoming decades, including in key hard-to-abate transport and industrial sectors. Unconventional oil (UO) has emerged as a sizeable contributor to meeting the global energy demand in the energy transition period. However, unfavorable circumstances compounded by the Covid-19 pandemic have intensified uncertainties and speculation regarding the future prospects of these resources. This mini-review explores prospects and challenges faced by UO development in the Covid-19 era, focusing on technical, economic, energy security, and environmental sustainability aspects. While UOs have been significantly affected by the pandemic in the short term, limited medium to long-term UO projections exist, with contrasted findings. The review reveals the multiplicity and complexity of interactions between the Covid-19 pandemic and the discussed UO aspects, the diversity of views, and conflicting short- and long-term goals of the energy industry.